2016
DOI: 10.4194/1303-2712-v16_1_22
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Various programs and organizations (IMO, UNEP, IOC UNESCO, FAO) and recently the EU MSFD recognized marine litter (ML) as an issue of global threat from environmental, economic, human health and safety, and aesthetic aspect. Among the efforts to combat the problem adequate monitoring and application of harmonized methodological approaches for quantification are essential. This research presents the results of a pilot assessment of bottom ML in the Black Sea during the MISIS Project Joint Black Sea Cruise (22-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…The decrease in concentration from coastal areas to the open ocean also supports the results of Experiment 2. As Moncheva et al (2016) stated, coastward along the 40 m isobath, the abundance of ML was generally much higher than on the continental shelf (see also Figure 4E).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The decrease in concentration from coastal areas to the open ocean also supports the results of Experiment 2. As Moncheva et al (2016) stated, coastward along the 40 m isobath, the abundance of ML was generally much higher than on the continental shelf (see also Figure 4E).…”
Section: Discussionsupporting
confidence: 65%
“…These surveys also identified a predominance of artificial polymer materials with densities ranging from 0.0587 ± 0.005 to 0.1343 ± 0.008 items m −2 . The pilot quantitative assessment of ML on the bottom performed by Moncheva et al (2016) demonstrated that (1) plastic was the most common debris material found in their area of study, which was very much in line with global findings, as well as with the results of Simeonova et al (2017), and (2) the abundance and distribution of ML showed considerable spatial variability. Understanding these phenomena calls for an in-depth examination of the methodologies for collection, classification and quantification of litter.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations